The Contribution of Gevorg Jahukyan to Comparative- Historical Study of the Armenian Language - AVETYAN, SARGIS (Bulletin of Yerevan University B: Philology, 2021)
The contribution of academician G. Jahukyan to comparative-historical study of the Armenian language can be characterized in broad lines as follows: a) application of new principles of describing and presenting comparative material, b) a thorough examination of the comparative grammar and all diachronic processes of Armenian, including the establishment of a number of phonological and morphological general patterns as well as many etymological observations, c) periodization of the whole pre-written history of Armenian, with the systematic description of reconstructable linguistic features characterizing the periods, d) a thorough areal characterization of Armenian in relation to the other dialects of Proto-Indo-European. Besides, G. Jahukyan made an important contribution to the Indo-European Linguistics, offering new solutions to a number of disputable problems, and to the study of the question of distant linguistic relationship as well.
Keywords: the establishment of a number of phonological and morphological general patterns, etymological observations, periodisation of the whole pre-written history of the Armenian language